2020
DOI: 10.20944/preprints202011.0364.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging Roles of Urine-Derived Components for the Management of Bladder Cancer: One Man’s Trash is Another Man’s Treasure

Abstract: Urinary bladder cancer (UBC) is the most common malignancy of the urinary tract in humans, with an estimated global prevalence of 1.1 million cases over 5 years1. Due to high rates of recurrence and resistance to chemotherapy, UBC is one of the most expensive cancers to treat, resulting in significant health care costs. There is, therefore, a critical need to develop innovative molecular and cellular tools to refine patient stratification and help predict response to treatment. Urine is an underused resource o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Kang et al, 2020 also illustrate the taxonomic classifications, with suggested treatments for different MIBC subtypes based on molecular biomarkers [ 109 ]. The combination of neoadjuvant therapy with immune checkpoint inhibitors (designed for suitable biomarker expression) is currently being tested and is expected to increase efficacy in treatments [ 110 ].…”
Section: Bladder Cancer Therapiesmentioning
confidence: 99%
“…Kang et al, 2020 also illustrate the taxonomic classifications, with suggested treatments for different MIBC subtypes based on molecular biomarkers [ 109 ]. The combination of neoadjuvant therapy with immune checkpoint inhibitors (designed for suitable biomarker expression) is currently being tested and is expected to increase efficacy in treatments [ 110 ].…”
Section: Bladder Cancer Therapiesmentioning
confidence: 99%
“…Canine bladder cancer organoids were previously described and exposed to anticancer drugs to describe their potential role in research and precision medicine (Elbadawy et al, 2019). Since canine bladder cancer is a well-established model for human muscle-invasive bladder cancer (Knapp et al, 2020), canine bladder cancer organoids represent a valuable model for translational preclinical research (Minkler et al, 2021). In addition, Elbadawy et al has recently described healthy canine bladder organoids (Elbadawy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Organoid technology has expanded recently from commonly used mice and human models to canines (Ambrosini et al, 2020;Chandra et al, 2019;Gabriel et al, 2022;Minkler et al, 2021;Mochel et al, 2018;Nantasanti et al, 2015) and few other vertebrates. However, the only reptilian (sensu lato) organoids (i.e., excluding those derived from chicken intestines (Zhao et al, 2022)), were generated from snake venom glands (Post et al, 2020), representing only a fraction of the vast Tree of Life.…”
Section: Introductionmentioning
confidence: 99%